Scaling in Super Element Model of Petroleum Reservoirs - Mazo, Alexandr; Potashev, Konstantin (Journal of physics. Conference series, 2019)
A feature of the super element two-phase flow model in an oil reservoir is the construction of a solution on computational grids with a spatial step of the order of the distance between wells (hundreds of meters) horizontally and of the order of the total thickness of the reservoir (tens of meters) vertically. To maintain the acceptable accuracy of the solution, the upscaling procedures are performed during the transition from a detailed geological to a large super element computational grid and downscaling during a reverse transition at the local refinement of the solution. The field of absolute permeability and functions of relative phase permeability are subject to upscaling. The downscaling procedure is applied to the grid saturation function on the super element grid to formulate the initial conditions for local refinement of the solution on the detailed computational grid. The paper describes ways to simplify and implement these procedures, taking into account the characteristic features of the geological structure and the process of oil reservoir development.